Defective formation of IgA memory B cells, Th1 and Th17 cells in symptomatic patients with selective IgA deficiency (2020)
ABSTRACT: Objective: Selective IgA deficiency (sIgAD) is the most common primary immunodeficiency in Western countries. Patients can suffer from recurrent infections and autoimmune diseases because of a largely unknown aetiology. To increase insights into the pathophysiology of the disease, we studied memory B and T cells and cytokine concentrations in peripheral blood. Methods: We analysed 30 sIgAD patients (12 children, 18 adults) through detailed phenotyping of peripheral B-cell, CD8+ T-cell and CD4+ T-cell subsets, sequence analysis of IGA and IGG transcripts, in vitro B-cell activation and blood cytokine measurements. Results: All patients had significantly decreased numbers of T-cell-dependent (TD; CD27+) and T-cell-independent (TI; CD27-) IgA memory B cells and increased CD21low B-cell numbers. IgM+IgD- memory B cells were decreased in children and normal in adult patients. IGA and IGG transcripts contained normal SHM levels. In sIgAD children, IGA transcripts more frequently used IGA2 than controls (58.5% vs. 25.1%), but not in adult patients. B-cell activation after in vitro stimulation was normal. However, adult sIgAD patients exhibited increased blood levels of TGF-β1, BAFF and APRIL, whereas they had decreased Th1 and Th17 cell numbers. Conclusion: Impaired IgA memory formation in sIgAD patients is not due to a B-cell activation defect. Instead, decreased Th1 and Th17 cell numbers and high blood levels of BAFF, APRIL and TGF-β1 might reflect disturbed regulation of IgA responses in vivo.These insights into B-cell extrinsic immune defects suggest the need for a broader immunological focus on genomics and functional analyses to unravel the pathogenesis of sIgAD.